Effects of plant diversity, soil microbial diversity, and network complexity on ecosystem multifunctionality in a tropical rainforest - Chen, Yanxuan; Huang, Xiaobo; Lang, Xuedong; Tang, Rong; Zhang, Rui; Li, Shuaifeng; Su, Jianrong (Frontiers in Plant Science, 2023)
Plant diversity and soil microbial diversity are important driving factors in sustaining ecosystem multifunctionality (EMF) in terrestrial ecosystems. However, little is known about the relative importance of plant diversity, soil microbial diversity, and soil microbial network complexity to EMF in tropical rainforests. Therefore, this study took the tropical rainforest in Xishuangbanna, Yunnan Province, China as the research object, and quantified various ecosystem functions such as soil organic carbon stock, soil nutrient cycling, biomass production, and water regulation in the tropical rainforest to explore the relationship and effect of plant diversity, soil microbial diversity, soil microbial network complexity and EMF. Our results exhibited that EMF decreased with increasing liana species richness, soil fungal diversity, and soil fungal network complexity, which followed a trend of initially increasing and then decreasing with soil bacterial diversity while increasing with soil bacterial network complexity. Soil microbial diversity and plant diversity primarily affected soil nutrient cycling. Additionally, liana species richness had a significant negative effect on soil organic carbon stocks. The random forest model suggested that liana species richness, soil bacterial network complexity, and soil fungal network complexity indicated more relative importance in sustaining EMF. The structural equation model revealed that soil bacterial network complexity and tree species richness displayed the significantly positive effects on EMF, while liana species richness significantly affected EMF via negative pathway. We also observed that soil microbial diversity indirectly affected EMF through soil microbial network complexity. Soil bulk density had a significant and negative effect on liana species richness, thus indirectly influencing EMF. Simultaneously, we further found that liana species richness was the main indicator of sustaining EMF in a tropical rainforest, while soil bacterial diversity was the primary driving factor. Our findings provide new insight into the relationship between biodiversity and EMF in a tropical rainforest ecosystem and the relative contribution of plant and soil microibal diversity to ecosystem function with increasing global climate change.